Fast track online shopping retail store using object character recognition image (OCR) - Khairunnisak, Noordin (2014)
Mobile application is one of the new technologies in information technology. Recent developments in the mobile phone industry created a lot of technologically that updated many applications of mobile that make our life easier than ever. The study of this application is between retail store sector and the application in mobile. Based on observation, the application in mobile at retail store is less uses or do not have been apply yet. The existing that using manually system in payment at retails store give less effectiveness of time. While in using pamphlet at retail store also give waste of paper and high budget. The aim and objective is for create application that can give advantage and facility to admin and customer. The objective is to create checkout shopping list in retail sector with barcode using mobile application and to develop an online catalog from QR code using mobile application. The methodologies that have been use in this application are software development life cycle.